2018
DOI: 10.1007/s11577-018-0518-x
|View full text |Cite
|
Sign up to set email alerts
|

Weiterbilden und Weiterkommen? Non-formale berufliche Weiterbildung und Arbeitsmarktmobilität in Deutschland

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Nevertheless, it is plausible that regular training participation also increases learning of skills that may become important once workers have to change into more learning-intensive jobs. In line with this, research consistently showed that training participation decreases the risk of unemployment (Dieckhoff 2007;Ebner and Ehlert 2018).…”
Section: Resultssupporting
confidence: 56%
“…Nevertheless, it is plausible that regular training participation also increases learning of skills that may become important once workers have to change into more learning-intensive jobs. In line with this, research consistently showed that training participation decreases the risk of unemployment (Dieckhoff 2007;Ebner and Ehlert 2018).…”
Section: Resultssupporting
confidence: 56%
“…For our underlying question, however, there are limitations with respect to AET. In contrast to schooling education, the general economic effect of AET is rather ambiguous and elusive, especially for the German context (for recent studies see Ebner and Ehlert 2018;Rüber and Bol 2017;Schwerdt et al 2012). Few studies report income effects from participation in AET or CVT, and for the most part the effects are very small.…”
Section: Economic Reasonsmentioning
confidence: 99%
“…While income effects and labour market returns of AET or informal learning activities have often been studied (e.g. Büchel and Pannenberg 2004;Ebner and Ehlert 2018;Rüber and Bol 2017;Schwerdt et al 2012), research on non-monetary returns has received less attention. Regarding non-monetary returns, it is assumed that adult learning can improve one's health, wellbeing, life satisfaction, social and political participation as well as literacy and numeracy skills (Schrader et al 2020).…”
mentioning
confidence: 99%
“…Hence, also from an individual perspective, gaining new skills and knowledge is vital for maintaining a competitive edge in today's dynamic labour markets. Although the evidence for positive returns to further education is mixed, research emphasizes particularly high returns from employer-provided job-related training (Ehlert, 2017) while reducing the risk of downward mobility (Ebner and Ehlert, 2018). However, employment interruptions and care obligations may reduce mothers' firm-specific training opportunities, while employers may have less incentive to invest in training.…”
Section: Introductionmentioning
confidence: 99%